Does capital gains tax aad to or detract from the South African tax system? - Maroun, Warren (My University, 2010)
In attempting to reform the tax system, the State has often relied on the principles of fairness (Vivian, 2006: 79). Indeed, part of the motivation for the introduction of Capital Gains Tax (CGT) was that it could assist with wealth redistribution and bolstering of State revenue to be used to improve the lot of the poor (SARS, 2001). In turn, this would, according to the Congress of South African Trade Unions (COSATU), mark the move to a more progressive tax system that was cognisant of the need for individuals to bear a proportionate share of the tax burden (COSATU, 2001). The principle of fairness and equality of taxes touched upon by the trade union and the South African Revenue Service (SARS) is not a new idea, having been dealt with earlier by economists such as Adam Smith (1776), and Mill (1848). Smith (1776:V.II.II) Stated the so-called first canon of tax dealing with fairness as follows: ‘The subjects of the State ought to contribute to the support of the government, as nearly as possible, in proportion to their respective abilities; that is, in proportion to revenue which they respectively enjoyed under the protection of the State. In the observation or neglect of this definition consists, what is called equality or inequality of taxation’ Approximately six years after CGT was first proposed this research seeks to explain what is meant by this classical principle of ‘fairness’ and re-examine the debate on whether or not CGT is aligned with this principle. To place the debate in a more modern context, it also seeks to consider whether key amendments to the Eighth Schedule to the Income Tax Act No.58 of 1962 (the Act) have made favourable ground in remedying perceived obstacles to the ideal of fairness identified when CGT was first proposed.
MComm, Faculty of Commerce, Law and Management, University of the Witwatersrand, 2007
Keywords: capital gains tax